2009
DOI: 10.1111/j.1439-0396.2008.00829.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of enzyme addition on the nutritive value of broiler diets containing hulled or dehulled Chinese double‐low rapeseed meals

Abstract: An in vitro and a feeding trial was conducted to investigate the effect of fibre-degrading enzymes A (xylanase + β-glucanase), B (xylanase) and C (xylanase + cellulase) on the nutritive value of broiler diets containing either hulled (22.5% and 23.5% for 4–21 days and 22–42 days of age, respectively) or dehulled (20% and 21.5%) Chinese double-low rapeseed meals (DLRM). Overall, in vitro digestibility of dry matter (DM) or neutral digestibility fibre (NDF) did not differ (p > 0.05) because of meal types; both c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 28 publications
0
10
0
1
Order By: Relevance
“…It is commonly accepted that the NDF represent most of the fiber fraction of feedstuff, which are poorly digested by poultry like ducks because of the lack of enzymes that can effectively degrade these complex carbohydrates (Villamide and San Juan, 1998;Adeola, 2006;Fang et al, 2008). It is also supported by the report that the digestibility of fiber in grain is less than 20% in poultry (Terence et al, 2000).…”
Section: Establishment Of Prediction Equations Of Tme From Ndfmentioning
confidence: 83%
See 1 more Smart Citation
“…It is commonly accepted that the NDF represent most of the fiber fraction of feedstuff, which are poorly digested by poultry like ducks because of the lack of enzymes that can effectively degrade these complex carbohydrates (Villamide and San Juan, 1998;Adeola, 2006;Fang et al, 2008). It is also supported by the report that the digestibility of fiber in grain is less than 20% in poultry (Terence et al, 2000).…”
Section: Establishment Of Prediction Equations Of Tme From Ndfmentioning
confidence: 83%
“…In the method of NDF analysis proposed by Van Soest, most of soluble nutrient were dissolved in neutral detergent, and the neutral detergent residue (i.e., NDF fraction) comprises a heterogenous mixture of structural (cellulose and most of hemicellulose) and nonstructural polysaccharides, lignin, and a few of protein and materials connected with cell wall (Chesson and Austin, 1998;Fang et al, 2007aFang et al, ,b, 2008. It is commonly accepted that the NDF represent most of the fiber fraction of feedstuff, which are poorly digested by poultry like ducks because of the lack of enzymes that can effectively degrade these complex carbohydrates (Villamide and San Juan, 1998;Adeola, 2006;Fang et al, 2008).…”
Section: Establishment Of Prediction Equations Of Tme From Ndfmentioning
confidence: 99%
“…Our results are in line with the findings of Vielma et al (1998), who observed no improvement in the whole-body protein content of rainbow trout, Oncorhynchus mykiss fed phytase supplemented diet. Improvement in the tissue CP content due to dietary cellulase enzyme in our study could either be due to increased protein digestibility (Fang et al 2009) and/ or improvement in dietary fiber digestion resulting in increased digestible energy, which in turn prevents the dietary protein from being utilized as energy, possibly a protein-sparing effect. Dietary cellulase (0.2%) significantly (P \ 0.05) enhanced the tissue ether extract contents by 10%.…”
Section: Discussionmentioning
confidence: 95%
“…It is expected that α-galacto-oligosaccharides are subjected to bacterial degradation due to lack of endogenous α-galactosidase activity in the host (Carré et al, 1995). Interestingly, there is no direct evidence that increased water insoluble NSP contents depress starch digestibility but may depress apparent protein digestibility in peas (Gabriel et al, 2008) and canola meal (Fang et al, 2009) due to the increase in bacterial protein losses (Carré et al, 1995) and protein and amino acid flows at the terminal ileum (Mateos et al, 2012). Thus, the effects of enzymes on the NSP component of the diet may affect patterns of ileal digestibility of protein, starch and lipids.…”
Section: Water-soluble and Insoluble Nspmentioning
confidence: 90%